Penerapan Asuhan Keperawatan Pada Ny. R Dengan Kanker Serviks Stadium IIIB Komplikasi Anemia Pengobatan Radioterapi Dalam Pemenuhan Kebutuhan Cairan Di Ruang Perawatan Lantai II Paviliun Iman Sudjudi RSPAD Gatot Soebroto - Kamilah, Lilis (UKInstitute, 2022)
Cervical cancer is a condition characterized by the growth of abnormal cells on the cervix, specifically in the epithelial layer or the outermost layer of the cervix, which is related to sexual activity. These cells can grow and develop into cancer cells. The purpose of this scientific paper is to determine the outcomes of nursing care implementation for Mrs. R, who has cervical cancer complicated by anemia due to radiotherapy, in meeting her fluid needs directly and comprehensively, including bio-psycho-social-spiritual aspects, with a nursing process approach. The data collection methods used in this paper include interviews, documentation, observation, and physical examination. The case study results show that Mrs. R has stage IIIB cervical cancer complicated by anemia, with symptoms of weakness, dizziness, and vaginal bleeding. The nursing issue identified in this case is fluid volume imbalance. After providing nursing care and conducting a case study on the theory and case, the conclusion is that the implementation of nursing care for Mrs. R with cervical cancer and anemia complications from radiotherapy involves fluid management interventions to improve fluid intake and increase hemoglobin concentration.